Spice-Derived Bioactive Ingredients: Potential Agents or Food Adjuvant in the Management of Diabetes Mellitus - Mohammed, Aminu; Islam, Md. Shahidul (Frontiers in Pharmacology, 2018)
Spices possess tremendous therapeutic potential including antidiabetic action, attributed to their bioactive ingredients. However, there is no study that critically reviewed the antidiabetic potency, safety and the bioavailability of the spice-derived bioactive ingredients (SDBI). Therefore, the aim of the study was to comprehensively review all published studies regarding the antidiabetic action of SDBI with the purpose to assess whether the ingredients are potential antidiabetic agents or adjuvant. Factors considered were concentration/dosages used, the extent of blood glucose reduction, the IC50 values, and the safety concern of the SDBI. From the results, cinnamaldehyde, curcumin, diosgenin, thymoquinone (TQ) and trigonelline were showed the most promising effects and hold future potentials as antidiabetic agents. Conclusively, future studies should focus on improving the tissue and cellular bioavailability of the promising SDBI to achieve greater potency. Additionally, clinical trials and toxicity studies are with these SDBI are warranted.